FUNGSI, MAKNA MOTIF PADA MASJID RAYA GANTIANG DI KOTA PADANG - IRMAWATI, Drs. Ady Rosa, M.Sn, Ir. Drs. Heldi, M.Si (Serupa The Journal of Art Education, 2014)
This study aimstofind outabout the function, meaning Motive In Gantiang Mosque in the city of Padang: This type of research is descriptive qualitative. The data source is the subject of where the data was obtained, 1) to describe or explain the function of motifon the mosque in the city of Padang Raya Gantiang 2) to determine the meaning of motif son Mosque Kingdom Gantiang. This data source is data obtained by interview and written do cument search. The collection of data in accordance with the analysis of the descriptive data processing techniques, describes the phenomenonas it is written in narrative form, which was obtained through field observations were done on Gantiang Mosque in the city of Padang. Kata kunci: Fungsi, Makna Motif